Neck recurrence in clinically node-negative oral cancer: 27-year experience at a single institution. (March 2018) - Mizrachi, Aviram; Migliacci, Jocelyn C.; Montero, Pablo H.; McBride, Sean; Shah, Jatin P.; Patel, Snehal G.; Ganly, Ian
Highlights: Up to 15% of patients with clinically N0 oral cancer may fail in the neck. Neck recurrence free survival is superior with elective neck dissection. Patients with neck recurrence are salvaged in 80% of cases but survival is poor. Surgery followed by adjuvant radiation or chemoradiation gives the best outcomes. Abstract: Objectives: Neck failure in patients with oral squamous cell carcinoma (OSCC) carries a poor outcome, yet the management of patients who initially present with clinically node-negative (cN0) neck is not clearly defined. Patients and methods: Retrospective review of patients with cN0 OSCC treated at Memorial Sloan Kettering Cancer Center from 1985 to 2012, focusing on rate, pattern and predictors of neck failure, salvage treatment, and survival outcomes. Results: Of 1, 302 patients, 806 (62%) underwent elective neck dissection (END) and 496 (38%) had observation. 190 patients (15%) developed neck recurrence. Median follow-up was 58.5 months (range 1–343); 5-year neck recurrence-free survival (NRFS) was 85% and 80% for the END and observation group respectively (p = .06). Patients with neck failure had poorer outcomes than patients without neck failure (5-year overall survival, 37% vs. 74% [p < .001]; disease-specific survival [DSS], 41% vs. 91% [p < .001]). Independent predictors of neck failure were smoking, primary tumor subsite (hard palate and upper gum), and extranodal extension. 87% of patients underwent salvage treatment (END: 81.1%; observation: 94%). Salvage surgery with adjuvant (chemo) radiation had better DSS than surgery alone or nonsurgical salvage. Conclusions: In our cohort of patients with initially cN0 OSCC triaged to END vs. observation using clinical parameters, 15% developed neck failure. Salvage treatment was feasible in most cases but survival was poorer compared to patients without neck failure. Surgery followed by adjuvant (chemo) radiation resulted in the best outcome.